CAD Guidebook: A Basic Manual for Understanding and Improving Computer-Aided Design, The - Schoonmaker, Stephen (CRC Press, 2009)
Covering how to implement, execute, adjust, and administer CAD systems, The CAD Guidebook presents fundamental principles and theories in the function, application, management, and design of 2- and 3-D CAD systems. It illustrates troubleshooting procedures and control techniques for enhanced system operation and development and includes an extensive glossary of key terms and concepts, and end-of-chapter review questions. The book is an essential reference for mechanical, manufacturing, industrial, software, computer, design, quality, and reliability engineers, and an excellent text for undergraduate and graduate students in these disciplines.